Virtual and augmented reality applications in sport and physical education learning: systematic literature review (2021–2026) - Kristian Burhan; Ifdil Ifdil; Rudyanto Rudyanto (Lentera Negeri, 2026)
Immersive technologies are becoming popular tools in sport and physical education. But the evidence for their teaching effectiveness is scattered across many fields. This systematic review looked at the design, implementation, effectiveness, and moderating factors of VR, AR, MR, and XR interventions in this area. The review followed PRISMA 2020 guidelines with a predefined protocol. We searched only Scopus because of its wide coverage and standardized metadata. That helped make the search transparent and reproducible. The search found 403 records. After removing duplicates and screening, 18 studies met the criteria. Two reviewers independently handled selection and data extraction. Their agreement was excellent, with Cohen's κ = 0.87. Methodological quality was checked using the Mixed Methods Appraisal Tool (MMAT 2018). Both reviewers did thematic synthesis separately before reaching consensus. Four main themes came out: (1) tactical and cognitive learning, (2) motor skill acquisition through augmented feedback, (3) curricular integration of immersive technologies, and (4) communication, socialization, and inclusion. Overall, these technologies boosted learner engagement, real-time feedback, motor skills, and tactical understanding. But their effectiveness depended on learner expertise, visuospatial ability, instructional design, and teacher competence. Still, using only Scopus and excluding grey literature might have caused publication bias and limited the evidence. Future work should focus on longitudinal studies, transfer of learning to real sport performance, and strong comparative trials across different educational settings.